Chronic low back pain – its association with lumbar spinal canal diameter – a cross-sectional hospital-based study in a tertiary care hospital in North Bengal - Mandal, Mahadeb; Chakraborty, Durga Prasad; Chattopadhyay, Aniruddha; Sarmah, Pulakesh; Bera, Nirmal Kumar (Asian Journal of Medical Sciences, 2022)
Background: Low back pain (LBP) is a very common cause of disability in working age adults, lumbar canal stenosis (LCS) being one of the chief anatomical correlates. However, number of studies seeking role of LCS in the origin of LBP are not many, particularly in India. Aims and Objectives: The aims of this study were to investigate LBP and its relation to lumbar canal diameter (LCD), also to evaluate the impact of psychosomatic factors on LBP. Materials and Methods: Eighty symptomatic (LBP) and 41 asymptomatic (without LBP) subjects were chosen and LCD for three lowest lumbar segments measured by 1.5 Tesla magnetic resonance imaging for both symptomatic and asymptomatic subjects was ascertained. Canal diameters of both groups were compared by Pearson’s Chi-square test. Pain intensity of patients was assessed using visual analog scale (VAS)-pain score. Using tests of normality and non-parametric test Spearman’s rank coefficient, correlation between VAS score (pain intensity) and lowest canal diameter of the cases was evaluated. To evaluate the role of psychosomatic factors in LBP, the number of subjects (LBP) with somatic symptoms disorder (SSD) score ≥8 was ascertained. Results: The results were as follows: (1) Significant association between presence of LCS (diameter <10 mm) and LBP (P=0.015). (2) No significant correlation between intensity of LBP (VAS score) and LCD. (3) 13.75% of LBP patients had SSD (Male 8% and Female 23.33%). Conclusion: LCS may be an important factor in the origin of LBP. More studies are needed in this regard and also seeking correlation between LBP and other anatomical factors. Psychosocial factors may play important role in the origin and maintenance of LBP.